Psychological Accounting of Managers in Allocating Training and Development Budget: An Organizational Ethnography - Dewa Putu Yohanes Agata L. Sandopart (CV. Global Cendekia Inti, 2024)
This study explores the practice of psychological accounting among managers in allocating training and development budgets, focusing on how managers subjectively and politically justify or reject training budgets beyond mere Return on Investment (ROI) considerations. Using an organizational ethnography approach at PT Manufaktur Nusantara (pseudonym) over six months, this research involved participant observation of 23 budget meeting sessions, in-depth interviews with 18 participants (32 interviews), and analysis of 47 internal documents. The findings reveal several main patterns, including a systematic difference in the mental categorization of training budgets between finance managers, who categorize them as discretionary expenses, and HR or line managers, who categorize them as strategic investments, which violates the fungibility assumption in neoclassical economics, the use of loss framing strategies that achieved a higher approval rate compared to gain framing, confirming the loss aversion principle, the influence of sunk cost fallacy in decisions to continue training programs, and the dominant role of personal relationships and informal negotiations in budget discussions. The novelty of this research lies in revealing that psychological accounting in organizations is multidimensional, socially constructed, and varies by functional position. This study contributes to extending mental accounting theory from the individual to the organizational level and provides practical implications for designing budgeting systems that consider behavioral factors.